PF.13 Fetal Echogenic Bowel: An 18-Year Review from the Wessex Region. (26th April 2013) - Walker, S; Kermack, A; Wellesley, D; Parasuraman, R
Abstract : Background: Echogenic bowel is a non-specific marker on antenatal ultrasound and is associated with a variety of underlying diagnoses and adverse fetal outcomes. Objectives: To evaluate fetal outcomes where echogenic bowel was identified on second trimester antenatal ultrasound. Method: Retrospective study of cases of echogenic bowel identified from the Fetal Medicine and Wessex Antenatally Detected Anomalies (WANDA) register between 1994 and 2012. Results: A total of 471 cases of echogenic bowel were identified over the 18-year period, of which 401 (85%) were isolated. Outcomes were available for 367 (91.5%) cases. 322 (80.2%) pregnancies resulted in a live birth, 21 (5.2%) had termination of pregnancy and 19 (4.7%) were complicated by intra-uterine demise. There were four (1.0%) neonatal deaths. Post-natal diagnosis was available for 358 (89.2%) cases, of which 259 (72.3%) were healthy, live-born infants. Cystic fibrosis and congenital cytomegalovirus infection was reported in ten (2.8%) and five (1.4%) respectively. Chromosomal abnormalities were present in 21 (5.9%), with Trisomy 21 the most prevalent 15 (4.2%). Intra-uterine growth restriction complicated 17 (4.8%) pregnancies. There were seven cases of intestinal atresia (2%). Conclusions: In our cohort the majority of cases had a good outcome and no postnatal abnormality. However the increased incidence of cystic fibrosis, chromosomal abnormalities and congenital infection highlights the importance of investigating this group. The prevalence of growth restriction advocates the consideration of serial growth ultrasound. These findings are useful in the counselling of parents and antenatal management following the identification of isolated echogenic bowel.